The Role Of Political Parties With The Worker Movement Rejecting The Omnibus Job Creation Law - Yarnes Imanuel Foni; Phil Aditya Perdana (Faculty of Law, University of Mataram, 2022)
This study aims to determine the role of political parties in the worker's movement to reject the ratification of the omnibus law on Job Creation. The approach used is qualitative. This research relies on primary data collection mainly obtained through interviews with resource persons or key informants. Data were collected in two ways. The first is to conduct a literature study and content analysis of various literature and reports in the print media related to research problems, and secondly, by conducting interviews with resource persons. The role of political parties in the rejection of the Job Creation Law must straighten out the functions first, rights, and obligations of political parties according to the provisions of the current political law in Indonesia. Political parties' functions, rights, and obligations have been outlined in Law Number 2 of 2011 concerning Political Parties. The function of political parties is regulated in 11. One of the functions related to the context that we are talking about is Article 11, point 2 subpoint (a), which states that political parties function as a means of: